A Practical Approach for Implementing the Additional Requirements of the ISO 15189:2012 Revision - (:unkn) unknown (IGI GLOBAL, 2015)
Medical laboratory services have a critical role as an integral component of patient care. The accreditation standard of ISO 15189, a guidance document, provides validation that a laboratory is competent to deliver accurate and reliable test results. This international standard has been evolving since 2003. Following the second publication (2007), the standard was released as a revised and updated version in 2012 (Medical laboratories -Requirements for quality and competence). The text of ISO 15189:2012 has been approved as EN ISO15189:2012. European Union members and associate countries agreed to accord it the status of a national standard by May 2013. Any conflicting national standards need to be withdrawn by November 2015 at the latest. The purpose of this chapter is to mark the differences between the two versions of the standards and to highlight the changes and additions that have been incorporated into ISO 15189:2012. A practical approach will be helpful for laboratories to make a smooth transition to the updated standard when revising their quality and technical documentation to meet the new requirements.